Meningkatkan Keterampilan Berbahasa Peserta Didik MAN 1 Mataram Melalui Pendekatan Konstruktivistik - Danu Saputra (Jurnal Paedagogy, 2021)
This study aims to improve students' language skills through a constructivist approach at MAN 1 Mataram. This research method uses classroom action research. The subjects of this study were students of class XI IBB MAN 1 Mataram. Data collection techniques in this study used tests, observations, and questionnaires. While the data analysis technique is quantitative and qualitative descriptive analysis. From this research, it can be concluded that the constructivist approach can improve students' language skills. The success of using this constructivist approach is shown by 36 out of 41 students in class XI IBB MAN 1 Mataram who managed to score above the KKM. This exceeded the target set before the study was conducted, which was 33 people. In addition, the percentage of students who chose to agree with positive statements related to language skills was 76%, exceeding the target set by 75%.